Commissioning of the 4-D treatment delivery system for organ motion management in synchrotron-based scanning ion beams. Issue 12 (December 2016) - Ciocca, Mario; Mirandola, Alfredo; Molinelli, Silvia; Russo, Stefania; Mastella, Edoardo; Vai, Alessandro; Mairani, Andrea; Magro, Giuseppe; Pella, Andrea; Donetti, Marco; Valvo, Francesca; Fossati, Piero; et al.
Highlights: Organ motion management represents a challenge in pencil-beam-scanning ion therapy. Interplay effect and range defect strongly deteriorate actual dose distribution. Combined gating and layered repainting are suitable to treat moving targets. Larger spot sizes represent a more favorable condition to minimize motion effect. Abstract: Purpose: The aim of this work was the commissioning of delivery procedures for the treatment of moving targets in scanning pencil beam hadrontherapy. Methods: EBT3 films fixed to the Anzai Respiratory Phantom were exposed to carbon ion scanned homogeneous fields (E = 332 MeV/u). To evaluate the interplay effect, field size and flatness for 3 different scenarios were compared to static condition: gated irradiation or repainting alone and combination of both. Respiratory signal was provided by Anzai pressure sensor or optical tracking system (OTS). End-exhale phase and 1 s gating window were chosen (2.5 mm residual motion). Dose measurements were performed using a PinPoint ionization chamber inserted into the Brainlab ET Gating Phantom. A sub-set of tests was also performed using proton beams. Results: The combination of gating technique and repainting (N = 5) showed excellent results (6.1% vs 4.3% flatness, identical field size and dose deviation within 1.3%). Treatment delivery time was acceptable. Dose homogeneity for gated irradiation alone was poor. Both Anzai sensor and OTS appeared suitable for providing respiratory signal. Comparisons between protons and carbon ions showed that larger beam spot sizes represent more favorable condition for minimizing motion effect. Conclusion: Results of measurements performed on different phantoms showed that the combination of gating and layered repainting is suitable to treat moving targets using scanning ion beams. Abdominal compression using thermoplastic masks, together with multi-field planning approach and multi-fractionation, have also been assessed as additional strategies to mitigate the effect of patient respiration in the clinical practice.